2003
DOI: 10.1021/jf026101t
|View full text |Cite
|
Sign up to set email alerts
|

Fine Structures and Physicochemical Properties of Starches from Chalky and Translucent Rice Kernels

Abstract: This work compared the molecular structures and physicochemical properties of starches obtained from chalky and translucent kernels of six rice cultivars. Starch samples were prepared according to a modified alkali steeping method. Crystallinity, pasting characteristics, and thermal properties were studied by X-ray diffraction, rapid viscosity analysis, and differential scanning calorimetry, respectively. Starch molecular size fractions (amylopectin, amylose, and intermediate material) were estimated by high-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
84
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(103 citation statements)
references
References 16 publications
16
84
2
1
Order By: Relevance
“…In the amylopectin fine structure, Lisle et al (2000) found no significant differences between chalky and translucent grains in the amount of high or low molecular weight glucans in the amylopectin fraction. By contrast, Patindol and Wang (2003) reported that chalky grains had shorter average chain length of amylopectin, higher percentage of short amylopectin branch chains, and lower percentage of long branch chains. The disagreement may be partially associated with the subtle difference in amylopection fine structure as well as the analytical method.…”
Section: Chemical Composition Of the Chalky Grainsmentioning
confidence: 86%
See 1 more Smart Citation
“…In the amylopectin fine structure, Lisle et al (2000) found no significant differences between chalky and translucent grains in the amount of high or low molecular weight glucans in the amylopectin fraction. By contrast, Patindol and Wang (2003) reported that chalky grains had shorter average chain length of amylopectin, higher percentage of short amylopectin branch chains, and lower percentage of long branch chains. The disagreement may be partially associated with the subtle difference in amylopection fine structure as well as the analytical method.…”
Section: Chemical Composition Of the Chalky Grainsmentioning
confidence: 86%
“…From analysis of the sucrose level in inferior and superior spikelets, Lisle et al (2000) suggested that chalkiness was not due to insufficient vascular supply of metabolites like sucrose and amino acids, but was more likely related to metabolic events within the developing grain that utilize carbon in sucrose for starch deposition. Patindol and Wang (2003) reported that chalky grains had shorter average chain length of amylopectin, which indicated that the formation of chalkiness might be associated with interruption in the step of chain length elongation. These two studies offer novel perspective for understanding the physiological reasons for chalkiness.…”
Section: Role Of Protein Bodies In Chalkiness Occurrencementioning
confidence: 99%
“…The QTLs controlling the composition of various protein fractions could be at the same chromosome locus. Patindol and Wang (2003) detected 18 chromosome portions for 19 single amino acids, with that located at the base of chromosome 1 being somewhat a stronger QTL bunch, comprising 19 single quantitative trait loci. There is a vast co-occurrence among the qualitative trait loci and the loci responsible for amino acid metabolic pathways, nitrogen absorption and transfer, and protein biosynthesis (Patindol and Wang 2003).…”
Section: Introductionmentioning
confidence: 99%
“…(González et al, 2004). Patindol and Wang (2003) studied the physicochemical properties of three nonwaxy, long-grain rices and found that different amylopectin structures could affect rice functionality, for example, the gelatinization, retrogradation and pasting behavior. Rice with an amylose content of 7.8% in comparison with four other rice varieties with 15.6-18.9% amylose content.…”
Section: Shamim Et Almentioning
confidence: 99%